Hepatoprotective Effects of Different Extracts From Triphala Against CCl4-Induced Acute Liver Injury in Mice - Wei, Xichuan; Luo, Chuanhong; He, Yanan; Huang, Haozhou; Ran, Fei; Liao, Wei; Tan, Peng; Fan, Sanhu; Cheng, Yuan; Zhang, Dingkun; Lin, Junzhi; Han, Li (Frontiers in Pharmacology, 2021)
Background: Triphala is a traditional polyherbal formula used in Indian Ayurvedic and Chinese Tibetan medicine. A wide range of biological activities have been attributed to Triphala, but the impact of various extraction methods on efficacy has not been determined. Purpose: The study aimed to evaluate Triphala extracts obtained by various methods for their hepatoprotective effects and molecular mechanisms in a mouse model of carbon tetrachloride (CCl4)-induced liver injury. Methods: HPLC fingerprinting was used to characterize the chemical characteristics of Triphala extracts obtained by (a) 0.5 h ultrasonication, (b) 2 h reflux, and (c) 4 h reflux. Hepatoprotective efficacy was evaluated in a mouse model of CCl4-induced liver damage. Serum levels of alanine transaminase (ALT) and aspartate aminotransferase (AST) were measured, as well as the liver antioxidant and inflammatory markers malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), TNF-α, and IL-6. Gene and protein expression of Nrf-2 signaling components Nrf-2, heme oxygenase (HO-1), and NADPH Quinone oxidoreductase (NQO-1) in liver tissue were evaluated by real-time PCR and western blotting. Results: Chemical analysis showed a clear difference in content between extracts produced by ultrasonic and reflux methods. The pharmacological analysis showed that all three Triphala extracts reduced ALT, AST, MDA, TNF-α, and IL-6 levels and increased SOD and GSH-Px. Triphala extracts also induced transcript and protein expression of Nrf-2, HO-1, and NQO-1. Conclusions: Triphala extract prevents CCl4-induced acute liver injury. The ultrasonic extract of Triphala was most effective, suggesting that hepatoprotection may be related to the larger tannins via activation of Nrf-2 signaling.